Education in identity - Rossiter, Graham (International journal of children's spirituality, 2007)
While identity has long been a prominent focus of education, and religious education, in Europe and Britain, little explicit attention has been given to it in Australia, even though its importance as an educational goal is implied. This paper reports on a project concerned with ‘education in identity’ which attempted to address this imbalance. A generic notion of education in identity is developed, underpinned by a conceptualisation of identity and of what constitutes identity health.